Drivers and Barriers for Water-Smart Solutions across 6 Cases: Policy and Governance, Deliverable 5.3 - Gomes, Carla (2022)
This is a report on Policy and Governance: Drivers and Barriers across 6 European Cases. It offers a preliminary overview of the main drivers and barriers related to the policy and governance dimensions across the six Living Labs of B-WaterSmart: Alicante (Spain), Bodø (Norway), East Frisia (Germany), Flanders (Belgium), Lisbon (Portugal) and Venice (Italy). It starts by providing an overview of the policy framework with implications for water management in the European Union, including the main plans and strategies related to adaptation to climate change and implementation of a circular economy, along with the nexus of water-energy resources waste. Furthermore, there is a section that describes succinctly the main models of water governance in Europe. The contents and conclusions of D5.3 will inform further work of WP5 – Society, Governance and Policy, namely Task 5.2 on Drivers and Barriers for the Implementation of B-WaterSmart Solutions, as well as Task 5.4 – Guidelines and recommendations for policy & regulation for water-smart systems, which has started in February 2022, and goes until the end of the project in August 2024. This report will also inform further work on proposals for innovative models of governance, in parallel with the Communities of Practice (CoP) of each LL (D5.5).